Invertebrate fragments associated with the preserved remains of Santa Maria Maddalena de’ Pazzi, Florence, Italy (17th century CE) - Piombino-Mascali, Dario; Hall, Martin J.R.; Sherwood, Danniella; Barclay, Maxwell V.L. (Medicina Historica, 2024)
This case study deals with some invertebrate fragments recovered during an inspection of the preserved remains of Santa Maria Maddalena de’ Pazzi in Florence, Italy. Sampling of these fragments was followed by their careful identification by microscopic examination and direct comparison with identified voucher specimens. Results showed that a current infestation affected the precious relic and that a conservation treatment was necessary for both religious and curatorial purposes.